Effects of the Indoor Environment on the Fraction of Exhaled Nitric Oxide in School-Aged Children - Thomas A Kovesi; Robert E Dales (Canadian Respiratory Journal)
BACKGROUND: The fractional concentration of exhaled nitric oxide (FeNO) appears to be a good marker for airway inflammation in children with asthma.